Politik Ekstra-Parlementer Digital dan Ketahanan Nasional: Media Sosial sebagai Instrumen Advokasi Gerakan Republik Maluku Selatan (RMS) - Frans Tory Damara Pradipta; Aliyah; Ramadhan, Gilang; Vikriadi, Khalid (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2026)
This study aims to analyze the representation of the political identity of the Republic of South Maluku (RMS) on Instagram. The study is motivated by the growing role of social media as a digital communication space that enables the construction and reproduction of political identities through symbols, narratives, and communication messages. This research employed a qualitative approach using Roland Barthes' semiotic analysis. Data were collected from Instagram posts containing historical narratives, symbols of struggle, and calls for collective action. The analysis was conducted through the levels of denotation, connotation, and myth to reveal the meanings embedded in the posts. The findings indicate that RMS political identity is represented through the reproduction of historical narratives, the commemoration of political figures, collective mobilization, and the use of symbols reflecting the group's struggle and identity. At the mythological level, Instagram posts construct a belief in the continuity of RMS political identity and struggle within digital spaces. The study concludes that Instagram functions not only as a medium for information dissemination but also as a platform for constructing and reinforcing political identity in digital communication.